2014
DOI: 10.7287/peerj.preprints.282v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Challenges in evaluation of pain and a pre-incisional line block

Abstract: 15Background: Our objective was to test the effectiveness of a local anesthetic line block 16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This was in line with our previous studies where no increase of either blood pressure or the vasopressin concentration was registered at opening of the abdomen during OHE in dogs. 5,17 These results are also in agreement with other studies in dogs where no beneficial effect on postoperative pain was found by infiltration of local anaesthesia at the incision, 43,44 by a shorter versus longer abdominal incision 45 or by reduction of the number of portals used in laparoscopic procedures. 46 Our interpretation is that minimized surgical stress and noxious stimuli at removal of ovaries are important to consider in development of new techniques for reduced postoperative pain.…”
Section: Discussionsupporting
confidence: 91%
“…This was in line with our previous studies where no increase of either blood pressure or the vasopressin concentration was registered at opening of the abdomen during OHE in dogs. 5,17 These results are also in agreement with other studies in dogs where no beneficial effect on postoperative pain was found by infiltration of local anaesthesia at the incision, 43,44 by a shorter versus longer abdominal incision 45 or by reduction of the number of portals used in laparoscopic procedures. 46 Our interpretation is that minimized surgical stress and noxious stimuli at removal of ovaries are important to consider in development of new techniques for reduced postoperative pain.…”
Section: Discussionsupporting
confidence: 91%